“GOLD” DEVELOPMENTS OF INSTITUTE OF METALS TECHNOLOGY OF THE NATIONAL ACADEMY OF SCIENCES OF BELARUS - E. M. Patuk; O. O. Stanulenis (Литьë и металлургия, 2008)
New developments and technologies of equipment of ITM NAN of Belarus at exhibitions, held on Moscow and Saint-Petersburg are presented.